Loneliness in motherhood - Maza, Bibiana (2001)
Maternity is here focused through three perspectives. The first one relates to personal data, the second one concerns maternity in general and its experiences and the third perspective deals with the medical environment and the necessary dialogue to host mothers in a friendly way, listen to them and encourage the natural bond. Reflections and experiences from La Casa de la Familia’s work are presented in relation to the way children and their families have been hosted at the Maternity Hospital in Lima.